Non-linear Thermo-Optical Properties of MoS2 Nanoflakes by Means of the Z-Scan Technique - Mirershadi, Soghra; Sattari, Farhad; Alipour, Afshin; Mortazavi, Seyedeh Zahra (Frontiers in Physics, 2020)
The nonlinear thermo-optical response of MoS2 nanoflakes was investigated using the Z-scan technique, employing TM00-mode with a CW-laser diode operating at a wavelength of 532 nm. The systems were found to exhibit a strong nonlinear response, dominated by nonlinear refraction. The effect of the thickness of the MoS2 layer, deposited on a glass substrate, on the nonlinear susceptibility was studied. Furthermore, in this study, the effects of modifying the thickness of the MoS2 nanoflakes on the nonlinear optical phenomena, such as self-focusing and self-defocusing was investigated for the first time. In all cases, the nonlinear absorption and refraction were determined. The corresponding third-order susceptibilities and second-order hyperpolarizability were calculated to be as large as 10-7 (esu) and 10-32 (esu), under laser excitation, respectively. Showing large third-order optical nonlinearity suggests the potential of the MoS2 nanoflakes in photonics applications.